2010
DOI: 10.2214/ajr.09.3064
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation for Short-Interval Follow-Up Examinations After a Probably Benign Assessment: Is Clinical Practice Consistent With BI-RADS Guidance?

Abstract: Objective American College of Radiology BI-RADS guidance suggests that women with a probably benign finding on mammography receive a management recommendation for short-interval follow-up; historically, radiologists in community practice have not consistently linked this assessment with short-interval follow-up. We evaluated predictors of discordance between probably benign assessments and short-interval follow-up recommendations. Materials and Methods We linked data on 196 radiologists who completed a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…If diagnosis did not occur within the time frame of the study, cases remained undiagnosed and time was calculated as the interval from their date of index abnormal mammogram to the last known visit date or the end of the study, whichever occurred first. For women with BI-RADS-3 mammogram results and time to diagnosis >180 days, time to definitive diagnosis was shifted backward 180 days to account for the ACR-recommended short-interval follow-up (repeat mammogram in six months) (Aiello Bowles 2010; Battaglia et al 2010). These data were derived from patient clinical records, scheduling information, and key informant interviews with healthcare personnel from the clinic.…”
Section: Methodsmentioning
confidence: 99%
“…If diagnosis did not occur within the time frame of the study, cases remained undiagnosed and time was calculated as the interval from their date of index abnormal mammogram to the last known visit date or the end of the study, whichever occurred first. For women with BI-RADS-3 mammogram results and time to diagnosis >180 days, time to definitive diagnosis was shifted backward 180 days to account for the ACR-recommended short-interval follow-up (repeat mammogram in six months) (Aiello Bowles 2010; Battaglia et al 2010). These data were derived from patient clinical records, scheduling information, and key informant interviews with healthcare personnel from the clinic.…”
Section: Methodsmentioning
confidence: 99%
“…The few published studies evaluating the frequency of BI-RADS 3 categorization in breast MRI screening report a rate of 6% to 12%. [12][13][14] Therefore, further research may be directed toward evaluating the indications for follow-up in baseline screening examinations to achieve the 6% to 12% range. A few studies have been performed evaluating the common indications for short-interval follow-up breast MRI and whether they are appropriate for such a recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have been performed evaluating the common indications for short-interval follow-up breast MRI and whether they are appropriate for such a recommendation. 12,[14][15][16][17] DeMartini et al 18 studied the impact of BPE on the diagnostic performance of breast MRI and found that increased BPE was associated with a higher abnormal interpretation rate (BI-RADS 0, 3, 4, or 5) and more likely to receive short-interval follow-up but was not related to significant differences in positive biopsy rate or cancer yield.…”
Section: Discussionmentioning
confidence: 99%
“…Some other American studies reported the proportion of lesions classified as BI-RADS category 3. Even if guidelines [1,2] recommend a short-interval follow-up for all women with these lesions, some authors [8,19] reported that the proportion of women with BI-RADS category 3 who received a short-interval follow-up recommendation was low in the 90's (40.3%-51%) and seems to be increasing over time (76% for the period 1996-2001 [20] and 91% for the period 2001-2006 [21]). However, because of this variation, our results cannot be compared to those BI-RADS studies.…”
Section: Discussionmentioning
confidence: 99%